Campylobacter jejuni causes colorectal cancer - Pascal Alain Gervaz; Álvaro De Campos; Alberto Caeiro (World Journal of Colorectal Surgery)
The incidence of colorectal cancer (CRC) has drastically increased in several Asian countries during the past four decades. These rapid epidemiological variations suggest that environmental parameters contribute to neoplastic transformation within the intestinal epithelium. A Western type of diet (rich in animal fat and proteins) is a recognized risk factor. In addition, there is a strong link between the type of diet and composition of the microbiota. These findings suggest that some bacteria may contribute to neoplastic transformation in the colon and rectum. However, a causal relationship between a specific microorganism and the development of CRC remains elusive. In this paper, we recapitulate the clinical evidence, suggesting that epigenetic transformation mediated by commensal bacteria is a prerequisite for tumor development in the large bowel. We review the experimental evidence, suggesting that a type of Campylobacter is likely to be involved in this neoplastic process. Campylobacter is highly prevalent in modern cattle and poultry farms and has the capacity to adhere to the colonic epithelium and contribute to genomic instability by releasing DNA-damaging toxins. Therefore, we hypothesize that the Campylobacter/Helicobacter group of bacteria may play a role in development of the two most common neoplasia of the digestive tract, i.e. adenocarcinoma of the colon and stomach, respectively.